Evaluation of systemic absorption and renal effects of topical ophthalmic flurbiprofen and diclofenac in healthy cats. (29th June 2015) - Lanuza, Rick; Rankin, Amy J.; KuKanich, Butch; Meekins, Jessica M.
Abstract: Objective: To investigate systemic absorption and renal effects of topically applied ophthalmic flurbiprofen and diclofenac in healthy cats. Animals studied: Twelve domestic shorthair cats. Procedures: Cats were randomly assigned to two treatment groups ( n = 6) and administered one drop (approximately 40 μL) of either flurbiprofen 0.03% or diclofenac 0.1% in both eyes four times daily (6 am, 12 pm, 6 pm, and 12 am) for 14 days. Blood samples were collected on days 0, 4, 8, 14, 16, and 17 and analyzed by liquid chromatography and mass spectrometry for flurbiprofen and diclofenac plasma concentrations. A complete blood count (CBC), serum chemistry, and urinalysis were analyzed at the beginning of the study (Day 0) and at the end of topical drug administration (Day 15). Results: Both drugs demonstrated systemic absorption. Flurbiprofen was detected (mean ± SD) at day 4 (237 ± 65 ng/mL), day 8 (396 ± 91 ng/mL), day 14 (423 ± 56 ng/mL), day 16 (350 ± 66 ng/mL), and day 17 (270 ± 62 ng/mL), and diclofenac was detected (mean ± SD) at day 4 (130 ± 44 ng/mL), day 8 (131 ± 25 ng/mL), day 14 (150 ± 36 mg/mL), and sporadically on day 16. Flurbiprofen plasma concentration decreased slowly over 48 h after the last dose. No clinically significant abnormalities were noted in the serum blood urea nitrogen, creatinine, or urine specific gravity at the end of topical drug administration compared to the beginning of the study. Conclusions: Flurbiprofen and diclofenac were systemically absorbed after topical administration four times daily to both eyes of healthy cats. Flurbiprofen reached higher plasma concentrations compared to diclofenac.